Amorphous state stability of plant vitrification solutions - Vozovyk, Krystyna; Bobrova, Olena; Prystalov, Anton; Shevchenko, Nadiya; Kuleshova, Larisa (Biologija, 2020)
Two critical factors for obtaining high viable biological samples after cryopreservation by vitrification method are cryoprotect-ant glass-forming ability while cooling and the stability of its amorphous state during warming. The present work is devoted to the study of the amorphous state stability of plant vitrification solutions (PVS) by differential scanning calorimetry me-thod. The objects of the study were PVS1 modified, PVS2, PVS3 modified, PVS4 and PVSN. The thermograms of PVSs, frozen in liquid nitrogen, were recorded at a warming rate of 0.5 deg/min. The glass transition temperatures of PVS1, PVS2 and PVS3 were –109.0°C, –115.3°C, and –93.9°C, respectively. Neither exo- nor endothermic peaks have been recorded, indicating no crystallization, at the cooling and the warming stages. PVS4 and PVSN thermograms, besides glass transition (–111.5°C and –110.0°C, correspondingly), showed crystallization from the amorphous state (devitrification) and ice melting peaks. Crystallization enthalpy of PVSN was 2.8 times higher compared to PVS4. This fact testifies that the crystalline phase was larger in PVSN compared to PVS4. It should be noted that crystallization in PVS4 and PVSN may be related to the low warming rate used during the experiment. At higher warming rates, this crystallization is likely to be avoided. Thus, PVS1, PVS2 and PVS3 have a high glass-forming ability and a stabile amorphous state. The amorphous state stability of PVS4 and PVSN is significantly lower compared to PVS1, PVS2, and PVS3.
Vozovyk K, Bobrova O, Prystalov A, Shevchenko N, Kuleshova L. Amorphous state stability of plant vitrification solutions. Biologija. 2020. 66(1): 47-53.
Keywords: plant vitrification solution; glass transition; amorphous state stability; devitrification; ice melting